CENPA acts as a prognostic factor that relates to immune infiltrates in gliomas - Wang, Bo; Wei, Wei; Long, Shengrong; Wang, Lesheng; Yang, Bin; Wu, Du; Li, Zhengwei; Li, Zhiqiang; Arshad, Muhammad; Li, Xiang; Chen, Jincao (Frontiers in Neurology, 2022)
Background. Glioma is the most common primary tumor of the central nervous system. CENPA (centromere protein A) plays an important role in ensuring that mitosis proceeds normally. The effect of CENPA on glioma is rarely reported. However, the current study aims to explore whether aberrant CENPA expression promotes glioma progression and the potential mechanisms involved. Methods. The GEPIA website, the Cancer Genome Atlas and the gene expression omnibus (GEO) were used for assessing the expression of CENPA in glioma, and the results were validated by real-time quantitative polymerase and immunohistochemical staining of clinical samples. The relationship between the expression and prognostic value of the CENPA gene in glioma was investigated by Kaplan-Meier survival analysis with RNA-seq and clinical profiles downloaded from the Chinese Glioma Genome Atlas (CGGA) and UCSC Xena. The association between CENPA and clinical characteristics was also evaluated. CCK8, wound-healing assay using two glioma cell lines, gene set enrichment analysis (GSEA), KEGG and GO enrichment analysis, analysis of immune infiltration and temozolomide sensitivity analysis and single-cell sequence analysis were performed to explore the underlying mechanisms of high CENPA expression and its effect on glioma development. Finally, we constructed a nomogram based on the expression of CENPA to predict patient prognosis. Results. CENPA was significantly upregulated in glioma tissue samples and correlated with patient prognosis. Moreover, downregulation of CENPA inhibited the migration and proliferation of glioma cells. Besides, the expression level of CENPA was significantly correlated with grade, PRS type, IDH mutation status and 1p19q codeletion status. Furthermore, CENPA could serve as an independent prognostic factor for glioma that mainly interferes with the normal progression of mitosis and regulates the tumor immune microenvironment favoring glioma development. Conclusion. CENPA may act as a prognostic factor in glioma patients and provide a novel target for the treatment of gliomas.